Clustering-Based Model Reduction for Glioma Graph Networks - Mlinarić, P.; Sokolikj, Z.; Talla, G.; Meyer-Baese, U.; Stadlbauer, Andreas; Malberg, H.; Na, C. H.; Juetten, K.; Wiestler, B.; Meyer-Baese, A. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2025)
We analyze structural and functional connectivity graphs for both healthy and glioma subjects by clustering-based model reduction to obtain a detailed understanding of these complex graphs. The reduced-order network is obtained by dividing the connected brain regions or nodes into disjoint clusters. Further, each cluster is replaced by a single new node in a reduced-size graph network. Several partitions are analyzed and evaluated based on model reduction errors.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Glioma; graph clustering; network systems; reduced-order modeling; structure-preserving

Controllability and Robustness of Functional and Structural Connectomic Networks in Glioma Patients - Meyer-Baese, Anke; Jütten, Kerstin; Meyer-Baese, Uwe; Amani, Ali Moradi; Malberg, Hagen; Stadlbauer, Andreas; Kinfe, Thomas Mehari; Na, Chuh Hyoun (Cancers, 2023)
Previous studies suggest that the topological properties of structural and functional neural networks in glioma patients are altered beyond the tumor location. These alterations are due to the dynamic interactions with large-scale neural circuits. Understanding and describing these interactions may be an important step towards deciphering glioma disease evolution. In this study, we analyze structural and functional brain networks in terms of determining the correlation between network robustness and topological features regarding the default-mode network (DMN), comparing prognostically differing patient groups to healthy controls. We determine the driver nodes of these networks, which are receptive to outside signals, and the critical nodes as the most important elements for controllability since their removal will dramatically affect network controllability. Our results suggest that network controllability and robustness of the DMN is decreased in glioma patients. We found losses of driver and critical nodes in patients, especially in the prognostically less favorable IDH wildtype (IDHwt) patients, which might reflect lesion-induced network disintegration. On the other hand, topological shifts of driver and critical nodes, and even increases in the number of critical nodes, were observed mainly in IDH mutated (IDHmut) patients, which might relate to varying degrees of network plasticity accompanying the chronic disease course in some of the patients, depending on tumor growth dynamics. We hereby implement a novel approach for further exploring disease evolution in brain cancer under the aspects of neural network controllability and robustness in glioma patients.
CRIS-Team Scopus Importer:2023-06-09
Keywords: controllability; critical nodes; driver set; glioma; robustness; structural and functional connectomics

Controllability of Functional and Structural Brain Networks - Amani, Ali Moradi; Tahmassebi, Amirhessam; Stadlbauer, Andreas; Meyer-Baese, Uwe; Noblet, Vincent; Blanc, Frederic; Malberg, Hagen; Meyer-Baese, Anke (Complexity, 2024)
Normal and aberrant cognitive functions are the result of the dynamic interplay between large-scale neural circuits. Describing the nature of these interactions has been a challenging task yet important for neurodegenerative disease evolution. Fusing modern dynamic graph network theory techniques and control theory applied on complex brain networks creates a new framework for neurodegenerative disease research by determining disease evolution at the subject level, facilitating a predictive treatment response and revealing key mechanisms responsible for disease alterations. It has been shown that two types of controllability—the average and the modal controllability—are relevant for the mechanistic explanation of how the brain navigates between cognitive states. Te average controllability favors highly connected areas which move the brain to easily reachable states, while the modal controllability favors weakly connected areas representative for difcult-to-reach states. We propose two different techniques to achieve these two types of controllability: a centrality measure based on a sensitivity analysis of the Laplacian matrix is employed to determine the average controllability, while graph distances form the basis of the modal controllability. Te concepts of “choosing the best driver set” and “graph distances” are applied to measure the average controllability and the modal controllability, respectively. Based on these new techniques, we obtain important disease descriptors that visualize alterations in the disease trajectory by revealing densely connected hubs or sparser areas. Our results suggest that these two techniques can accurately describe the different node roles in controlling trajectories of brain networks.
CRIS-Team Scopus Importer:2024-10-25

Deep brain stimulation and stereotactic-assisted brain graft injection targeting fronto-striatal circuits for Huntington's disease: an update - Kinfe, Thomas Mehari; Del Vecchio, Alessandro; Nüssel, Martin; Zhao, Yining; Stadlbauer, Andreas; Buchfelder, Michael (Expert review of neurotherapeutics, 2022)
Introduction: Huntington's Disease as progressive neurological disorders associated with motor, behavioral, and cognitive impairment poses a therapeutic challenge in case of limited responsiveness to established therapeutics. Pallidal deep brain stimulation and neurorestorative strategies (brain grafts) scoping to modulate fronto-striatal circuits have gained increased recognition for the treatment of refractory Huntington's disease (HD).
CRIS-Team WoS Importer:2022-07-08
Keywords: Huntington´s disease; fronto-striatal circuits; chorea; parkinsonism; dystonia; globus pallidus externus/internus; deep-brain stimulation; striatum; brain grafts; unified Huntington´s disease rating scale (UHDRS); chorea; safety; efficacy; quality of life

Differences in metabolism of fiber tract alterations in gliomas: A combined fiber density mapping and magnetic resonance spectroscopic imaging study - Stadlbauer, Andreas; Hammen, Thilo; Buchfelder, Michael; Bachmair, Johanna; Dörfler, Arnd; Nimsky, Christopher; Ganslandt, Oliver (Neurosurgery, 2012)
BACKGROUND: Gliomas propagate diffusely throughout and along white matter structures. Glioma-related changes in structural integrity and metabolism are not detectable by standard magnetic resonance (MR) imaging. OBJECTIVE: To investigate differences in the metabolism of fiber tract alterations between gliomas grade II to IV by correlation of fiber density values with metabolite concentrations measured by fiber density mapping and MR spectroscopic imaging. METHODS: Fiber density mapping and MR spectroscopic imaging were performed in 48 patients with gliomas WHO grade II to IV. Fiber density mapping data were used to define fiber tracts in tumoral and peritumoral areas. Structural integrity of fiber tracts was assessed as fiber density ipsilateral-to-contralateral ratio (FD ICR). Metabolite concentrations for choline-containing compounds and N-acetyl-aspartate were computed and correlated to FD ICR values after coregistration with anatomic MR imaging. RESULTS: In tumoral areas, choline-containing compound concentrations of altered fiber tracts were significantly different between low- and high-grade glioma and showed different courses for the correlations of FD ICR and choline-containing czeompounds. In high-grade glioma, increasing fiber destruction was associated with a massive progression in cell membrane proliferation. Peritumoral fiber structures showed significantly decreased N-acetyl-aspartate concentrations for all patients, but only patients with glioblastoma multiforme had significantly decreased fiber density compared with the contralateral side. Glioma grades II and III had significantly higher peritumoral FD ICR than glioblastoma multiforme. CONCLUSION: A multiparametric MR imaging strategy providing information about both structural integrity and metabolism of the tumor is required for detailed assessment of glioma-related fiber tract alterations, which in turn is essential for treatment planning. Copyright © 2012 by the Congress of Neurological Surgeons.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Brain tumor; Diffusion tensor; Fiber density; Magnetic resonance spectroscopy

Dynamical graph networks may aid in phenotyping prognostically different brain tumor types - Meyer-Baese, Anke; Juetten, Kerstin; Meyer-Baese, Uwe; Stadlbauer, Andreas; Kinfe, Thomas Mehari; Na, Chuh Hyoun (Proceedings of SPIE - The International Society for Optical Engineering, 2022)
Diffuse infiltrative glioma are considered as a systemic brain disorder and produce alterations on cerebral functional and structural integrity beyond the tumor location. These alterations are the result of the dynamic interplay between large-scale neural circuits. Describing the nature of these interactions has been a challenging task yet important for glioma disease evolution. Modern dynamic graph network theory techniques and control theory applied to these structural and functional networks opens a new research avenue for understanding the dynamical properties and differences between healthy controls and glioma patients. It has been shown that controllability is relevant for providing the mechanistic explanation of how the brain navigates between cognitive states. We believe that it is also relevant for describing the connectomic alterations in glioma and the differences among subtypes and healthy controls. The nodes that are needed to control these networks and influence them to any state are called driver nodes. We determined the driver nodes of the Default-Mode Network (DMN) for resting-state functional connectivity (FC) and diffusion-MRI-based structural connectivity (SC) (comprising edge-weight (EW) and fractional anisotropy (FA)) networks in isodehydrogenase mutated (IDHmut) and wildtype (IDHwt) patients and healthy controls. Our results show that healthy controls have a better controllability for both FC and SC, and that structural connectomic dynamical aberrations are more pronounced in glioma patients than functional connectomic alterations.
CRIS-Team Scopus Importer:2022-12-02
Keywords: Brain Networks; Default-Mode Network; Driver Nodes; Functional Connectivity; Glioma; Structural

Emerging roles of leptin in Parkinson's disease: Chronic inflammation, neuroprotection and more? - Regensburger, Martin; Rasul Chaudhry, Shafqat; Yasin, Hammad; Zhao, Yining; Stadlbauer, Andreas; Buchfelder, Michael; Kinfe, Thomas Mehari (Brain Behavior and Immunity, 2023)
An increasing body of experimental evidence implicates a relationship between immunometabolic deterioration and the progression of Parkinson's disease (PD) with a dysregulation of central and peripheral neuroinflammatory networks mediated by circulating adipokines, in particular leptin. We screened the current literature on the role of adipokines in PD. Hence, we searched known databases (PubMed, MEDLINE/OVID) and reviewed original and review articles using the following terms: “leptin/ObR”, “Parkinson's disease”, “immune-metabolism”, “biomarkers” and “neuroinflammation”. Focusing on leptin, we summarize and discuss the existing in vivo and in vitro evidence on how adipokines may be protective against neurodegeneration, but at the same time contribute to the progression of PD. These components of the adipose brain axis represent a hitherto underestimated pathway to study systemic influences on dopaminergic degeneration. In addition, we give a comprehensive update on the potential of adjunctive therapeutics in PD targeting leptin, leptin-receptors, and associated pathways. Further experimental and clinical trials are needed to elucidate the mechanisms of action and the value of central and peripheral adipose-immune-metabolism molecular phenotyping in order to develop and validate the differential roles of different adipokines as potential therapeutic target for PD patients.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Immunometabolism; Leptin; Neurodegeneration; Neuroinflammation; ObR; Parkinson‘s disease

Immunometabolic Profiling of Chronic Subdural Hematoma through Untargeted Mass Spectrometry Analysis: Preliminary Findings of a Novel Approach - Kipele, Maria William; Buchfelder, Michael; Taudte, R. Verena; Stadlbauer, Andreas; Kinfe, Thomas Mehari; Bozhkov, Yavor (Diagnostics, 2023)
Objective: Metabolomics has growing importance in the research of inflammatory processes. Chronic subdural hematoma (cSDH) is considered to be, at least in part, of inflammatory nature, but no metabolic analyses yet exist. Therefore, a mass spectrometry untargeted metabolic analysis was performed on hematoma samples from patients with cSDH. Methods: A prospective analytical cross-sectional study on the efficacy of subperiosteal drains in cSDH was performed. Newly diagnosed patients had the option of granting permission for the collection of a hematoma sample upon its removal. The samples were analyzed using liquid chromatography–mass spectrometry to obtain different types of metabolites from diverse biochemical classes. The statistical analysis included data cleaning, imputation, and log transformation, followed by PCA, PLS-DA, HCA, and ANOVA. The postoperative course of the disease was followed for 3 months. The metabolite concentrations in the hematoma fluid were compared based on whether a recurrence of the disease was recorded within this time frame. Results: Fifty-nine samples from patients who were operated on because of a cSDH were gathered. Among those, 8 samples were eliminated because of missing metabolites, and only 51 samples were analyzed further. Additionally, 39 samples were from patients who showed no recurrence over the course of a 3-month follow-up, and 12 samples were from a group with later recurrence. We recorded a noticeable drop (35%) in the concentration of acylcarnitines in the ”recurrence group“, where 10 of the 22 tested metabolites showed a significant reduction (p < 0.05). Furthermore, a noticeable reduction in different Acyl-CoA-dehydrogenases was detected (VLCAD-deficiency p < 0.05, MCAD-deficiency p = 0.07). No further changes were detected between both populations. Conclusions: The current study presents a new approach to the research of cSDH. The measurements presented us with new data, which, to date, are without any reference values. Therefore, it is difficult to interpret the information, and our conclusions should be considered to be only speculative. The results do, however, point in the direction of impaired fatty acid oxidation for cases with later recurrence. As fatty acid oxidation plays an important role in inflammatory energy metabolism, the results suggest that inflammatory processes could be aggravated in cases with recurrence. Because our findings are neither proven through further analyses nor offer an obvious therapy option, their implications would not change everyday practice in the management of cSDH. They do, however, present a further possibility of research that might, in the future, be relevant to the therapy.
CRIS-Team Scopus Importer:2023-11-24
Keywords: chronic subdural hematoma; inflammation; metabolic profile; metabolomics

JunB is a key regulator of multiple myeloma bone marrow angiogenesis - Fan, Fengjuan; Malvestiti, Stefano; Vallet, Sonia; Lind, Judith; Garcia-Manteiga, Jose Manuel; Morelli, Eugenio; Jiang, Qinyue; Seckinger, Anja; Hose, Dirk; Goldschmidt, Hartmut; Stadlbauer, Andreas; Sun, Chunyan; et al. (Leukemia, 2021)
Bone marrow (BM) angiogenesis significantly influences disease progression in multiple myeloma (MM) patients and correlates with adverse prognosis. The present study shows a statistically significant correlation of the AP-1 family member JunB with VEGF, VEGFB, and IGF1 expression levels in MM. In contrast to the angiogenic master regulator Hif-1 alpha, JunB protein levels were independent of hypoxia. Results in tumor-cell models that allow the induction of JunB knockdown or JunB activation, respectively, corroborated the functional role of JunB in the production and secretion of these angiogenic factors (AFs). Consequently, conditioned media derived from MM cells after JunB knockdown or JunB activation either inhibited or stimulated in vitro angiogenesis. The impact of JunB on MM BM angiogenesis was finally confirmed in a dynamic 3D model of the BM microenvironment, a xenograft mouse model as well as in patient-derived BM sections. In summary, in continuation of our previous study (Fan et al., 2017), the present report reveals for the first time that JunB is not only a mediator of MM cell survival, proliferation, and drug resistance, but also a promoter of AF transcription and consequently of MM BM angiogenesis. Our results thereby underscore worldwide efforts to target AP-1 transcription factors such as JunB as a promising strategy in MM therapy.
CRIS-Team WoS Importer:2021-05-28

Large-Scale Graph Networks and AI Applied to Medical Image Data Processing - Meyer-Baese, Anke; Foo, Simon; Tahmassebi, Amirhessam; Meyer-Baese, Uwe; Amani, Ali Moradi; Götz, Theresa; Leithner, Doris; Stadlbauer, Andreas; Pinker-Domenig, Katja (COMPUTATIONAL IMAGING V, 2020)
CRIS-Team WoS Importer:2021-07-30

Melatonin moderates the triangle of chronic pain, sleep architecture and immunometabolic traffic - Chaudhry, Shafqat R.; Stadlbauer, Andreas; Buchfelder, Michael; Kinfe, Thomas Mehari (Biomedicines, 2021)
Preclinical as well as human studies indicate that melatonin is essential for a physiological sleep state, promotes analgesia and is involved in immunometabolic signaling by regulating neuroin-flammatory pathways. Experimental and clinical neuromodulation studies for chronic pain treatment suggest that neurostimulation therapies such as spinal cord stimulation, vagus nerve stimulation and dorsal root ganglion stimulation have an impact on circulating inflammatory mediators in blood, cerebrospinal fluid and saliva. Herein, we provide an overview of current literature relevant for the shared pathways of sleep, pain and immunometabolism and elaborate the impact of melatonin on the crossroad of sleep, chronic pain and immunometabolism. Furthermore, we discuss the potential of melatonin as an adjunct to neurostimulation therapies. In this narrative review, we addressed these questions using the following search terms: melatonin, sleep, immunometabolism, obesity, chronic pain, neuromodulation, neurostimulation, neuroinflammation, molecular inflammatory phenotyping. So far, the majority of the published literature is derived from experimental studies and studies specifically assessing these relationships in context to neurostimulation are sparse. Thus, the adjunct potential of melatonin in clinical neurostimulation has not been evaluated under the umbrella of randomized-controlled trials and deserves increased attention as melatonin interacts and shares pathways relevant for noninvasive and invasive neurostimulation therapies.
CRIS-Team Scopus Importer:2021-08-20
Keywords: Augmentation of neurostimulation therapies; Central and peripheral neuroinflammation pathways; Chronic pain; Immune-metabolism; Melatonin; Sleep

Physiological MRI Biomarkers in the Differentiation Between Glioblastomas and Solitary Brain Metastases - Heynold, Elisabeth; Zimmermann, Max; Hore, Nirjhar; Buchfelder, Michael; Dörfler, Arnd; Stadlbauer, Andreas; Kremenevski, Natalia (Molecular Imaging and Biology, 2021)
Purpose: Glioblastomas (GB) and solitary brain metastases (BM) are the most common brain tumors in adults. GB and BM may appear similar in conventional magnetic resonance imaging (cMRI). Their management strategies, however, are quite different with significant consequences on clinical outcome. The aim of this study was to evaluate the usefulness of a previously presented physiological MRI approach scoping to obtain quantitative information about microvascular architecture and perfusion, neovascularization activity, and oxygen metabolism to differentiate GB from BM. Procedures: Thirty-three consecutive patients with newly diagnosed, untreated, and histopathologically confirmed GB or BM were preoperatively examined with our physiological MRI approach as part of the cMRI protocol. Results: Physiological MRI biomarker maps revealed several significant differences in the pathophysiology of GB and BM: Central necrosis was more hypoxic in GB than in BM (30 %; P = 0.036), which was associated with higher neovascularization activity (65 %; P = 0.043) and metabolic rate of oxygen (48 %; P = 0.004) in the adjacent contrast-enhancing viable tumor parts of GB. In peritumoral edema, GB infiltration caused neovascularization activity (93 %; P = 0.018) and higher microvascular perfusion (30 %; P = 0.022) associated with higher tissue oxygen tension (33 %; P = 0.020) and lower oxygen extraction from vasculature (32 %; P = 0.040). Conclusion: Our physiological MRI approach, which requires only 7 min of extra data acquisition time, might be helpful to noninvasively distinguish GB and BM based on pathophysiological differences. However, further studies including more patients are required.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Angiogenesis; Brain metastasis; Glioblastoma; Hypoxia; Physiological MRI

Prediction of the Topography of the Corticospinal Tract on T1-Weighted MR Images Using Deep-Learning-Based Segmentation - Barany, Laszlo; Hore, Nirjhar; Stadlbauer, Andreas; Buchfelder, Michael; Brandner, Sebastian (Diagnostics, 2023)
Introduction: Tractography is an invaluable tool in the planning of tumor surgery in the vicinity of functionally eloquent areas of the brain as well as in the research of normal development or of various diseases. The aim of our study was to compare the performance of a deep-learning-based image segmentation for the prediction of the topography of white matter tracts on T1-weighted MR images to the performance of a manual segmentation. Methods: T1-weighted MR images of 190 healthy subjects from 6 different datasets were utilized in this study. Using deterministic diffusion tensor imaging, we first reconstructed the corticospinal tract on both sides. After training a segmentation model on 90 subjects of the PIOP2 dataset using the nnU-Net in a cloud-based environment with graphical processing unit (Google Colab), we evaluated its performance using 100 subjects from 6 different datasets. Results: Our algorithm created a segmentation model that predicted the topography of the corticospinal pathway on T1-weighted images in healthy subjects. The average dice score was 0.5479 (0.3513–0.7184) on the validation dataset. Conclusions: Deep-learning-based segmentation could be applicable in the future to predict the location of white matter pathways in T1-weighted scans.
CRIS-Team Scopus Importer:2023-03-24
Keywords: corticospinal tract; deep learning; magnetic resonance imaging; tractography

Real-time imaging of glutamate transients in the extracellular space of acute human brain slices using a single-wavelength glutamate fluorescence nanosensor - Brandner, Sebastian; Aicher, Simon; Schröter, Sarah; Swierzy, Izabela; Kinfe, Thomas Mehari; Buchfelder, Michael; Maslarova, Anna; Stadlbauer, Andreas (Scientific Reports, 2022)
Glutamate is the most important excitatory neurotransmitter in the brain. The ability to assess glutamate release and re-uptake with high spatial and temporal resolution is crucial to understand the involvement of this primary excitatory neurotransmitter in both normal brain function and different neurological disorders. Real-time imaging of glutamate transients by fluorescent nanosensors has been accomplished in rat brain slices. We performed for the first time single-wavelength glutamate nanosensor imaging in human cortical brain slices obtained from patients who underwent epilepsy surgery. The glutamate fluorescence nanosensor signals of the electrically stimulated human cortical brain slices showed steep intensity increase followed by an exponential decrease. The spatial distribution and the time course of the signal were in good agreement with the position of the stimulation electrode and the dynamics of the electrical stimulation, respectively. Pharmacological manipulation of glutamate release and reuptake was associated with corresponding changes in the glutamate fluorescence nanosensor signals. We demonstrated that the recently developed fluorescent nanosensors for glutamate allow to detect neuronal activity in acute human cortical brain slices with high spatiotemporal precision. Future application to tissue samples from different pathologies may provide new insights into pathophysiology without the limitations of an animal model.
CRIS-Team Scopus Importer:2022-03-25

Tissue hypoxia and alterations in microvascular architecture predict glioblastoma recurrence in humans - Stadlbauer, Andreas; Kinfe, Thomas Mehari; Eyüpoglu, Ilker Yasin; Zimmermann, Max; Kitzwoegerer, Melitta; Podar, Klaus; Buchfelder, Michael; Heinz, Gertraud; Oberndorfer, Stefan; Marhold, Franz (Clinical Cancer Research, 2021)
Purpose: Insufficient control of infiltrative glioblastoma (GBM) cells is a major cause of treatment failure and tumor recurrence. Hence, detailed insights into pathophysiologic changes that precede GBM recurrence are needed to develop more precise neuroimaging modalities for tailored diagnostic monitoring and therapeutic approaches. Experimental Design: Overall, 168 physiologic MRI follow-up examinations of 56 patients with GBM who developed recurrence after standard therapy were retrospectively evaluated, that is, two post-standard-therapeutic follow-ups before and one at radiological recurrence. MRI biomarkers for microvascular architecture and perfusion, neovascularization activity, oxygen metabolism, and hypoxia were determined for brain areas that developed in the further course into recurrence and for the recurrent GBM itself. The temporal pattern of biomarker changes was fitted with locally estimated scatterplot smoothing functions and analyzed for pathophysiologic changes preceding radiological GBM recurrence. Results: Our MRI approach demonstrated early pathophysiologic changes prior to radiological GBM recurrence in all patients. Analysis of the time courses revealed a model for the pathophysiology of GBM recurrence: 190 days prior to radiological recurrence, vascular cooption by GBM cells induced vessel regression, detected as decreasing vessel density/perfusion and increasing hypoxia. Seventy days later, neovascularization activity was upregulated, which reincreased vessel density and perfusion. Hypoxia, however, continued to intensify for 30 days and peaked 90 days before radiological recurrence. Conclusions: Hypoxia may represent an early sign for GBM recurrence. This might become useful in the development of new combined diagnostic-therapeutic approaches for tailored clinical management of recurrent GBM. Further preclinical and in-human studies are required for validation and evaluation.
CRIS-Team Scopus Importer:2021-04-09

Treatment with Cyclic AMP Activators Reduces Glioblastoma Growth and Invasion as Assessed by Two-Photon Microscopy - Wartchow, Krista Mineia; Schmid, Benjamin; Tripal, Philipp; Stadlbauer, Andreas; Buchfelder, Michael; Goncalves, Carlos-Alberto; Kleindienst, Andrea (Cells, 2021)
(1) Background: Despite progress in surgery and radio-chemotherapy of glioblastoma (GB), the prognosis remains very poor. GB cells exhibit a preference for hypoxia to maintain their tumor-forming capacity. Enhancing oxidative phosphorylation-known as the anti-Warburg effect-with cyclic AMP activators has been demonstrated to drive GB cells from proliferation to differentiation thereby reducing tumor growth in a cell culture approach. Here we re-evaluate this treatment in a more clinically relevant model. (2) Methods: The effect of treatment with dibutyryl cyclic AMP (dbcAMP, 1 mM) and the cAMP activator forskolin (50µM) was assessed in a GB cell line (U87GFP+, 104 cells) co-cultured with mouse organotypic brain slices providing architecture and biochemical properties of normal brain tissue. Cell viability was determined by propidium-iodide, and gross metabolic effects were excluded in the extracellular medium. Tumor growth was quantified in terms of area, volume, and invasion at the start of culture, 48 h, 7 days, and 14 days after treatment. (3) Results: The tumor area was significantly reduced following dbcAMP or forskolin treatment (F2,249 = 5.968, p = 0.0029). 3D volumetric quantification utilizing two-photon fluorescence microscopy revealed that the treated tumors maintained a spheric shape while the untreated controls exhibited the GB typical invasive growth pattern. (4) Conclusions: Our data demonstrate that treatment with a cAMP analog/activator reduces GB growth and invasion.
CRIS-Team Scopus Importer:2021-04-16
Keywords: 2-photon-microscopy; glioblastoma; oxidative phosphorylation; treatment; Warburg effect